Souls in dispute : converso identities in Iberia and the Jewish diaspora, 1580-1700 - Graizbord, David L. (Jewish culture and contexts., 2004)
Throughout the Middle Ages, the Iberian Peninsula was home to a rich cultural mix of Christians, Jews, and Muslims. At the end of the fifteenth century, however, the last Islamic stronghold fell, and Jews were forced either to convert to Christianity or to face expulsion. Thousands left for other parts of Europe and Asia, eventually establishing Sephardic communities in Amsterdam, Venice, Istanbul, southwestern France, and elsewhere. More than a hundred years after the expulsion, some Judeoconversos--descendants of Spanish and Portuguese Jews who had converted to Christianity--were forced to flee the Iberian Peninsula once again to avoid ethnic and religious persecution. Many of them joined the Sephardic Diaspora and embraced rabbinic Judaism. Later some of these same people or their descendants returned to Iberian lands temporarily or permanently and, in a twist that Jewish authorities considered scandalous, reverted to Catholicism. Among them were some who betrayed their fellow conversos to the Holy Office. In Souls in Dispute, David L. Graizbord unravels this intriguing history of the renegade conversos and constructs a detailed and psychologically acute portrait of their motivations. Through a probing analysis of relevant inquisitorial documents and a wide-ranging investigation into the history of the Sephardic Diaspora and Habsburg Spain, Graizbord shows that, far from being simply reckless and vindictive, the renegades used their double acts of border crossing to negotiate a dangerous and unsteady economic environment: so long as their religious and social ambiguity remained undetected, they were rewarded with the means for material survival. In addition, Graizbord sheds new light on the conflict-ridden transformation of makeshift Jewish colonies of Iberian expatriates--especially in the borderlands of southwestern France--showing that the renegades failed to accommodate fully to a climate of conformity that transformed these Sephardic groups into disciplined communities of Jews. Ultimately, Souls in Dispute explains how and why Judeoconversos built and rebuilt their religious and social identities, and what it meant to them to be both Jewish and Christian given the constraints they faced in their time and place in history.